Donor-funded research: permissible, not perfect - King, Mike (Journal of medical ethics, 2019)
Donor-funded research is research funded by private donors in exchange for research-related benefits, such as trial participation or access to the trial intervention. This has been pejoratively referred to as ‘pay to play’ research, and criticised as unethical. We outline three models of donor-funded research, and argue for their permissibility on the grounds of personal liberty, their capacity to facilitate otherwise unfunded health research and their consistency with current ethical standards for research. We defend this argument against objections that donor-funded research is wrongly exploitative, unfair and undermines the public good of medical research. Our conclusion is that, like all human subjects research, donor-funded research should be regulated via standard health research legislation/guidelines and undergo Research Ethics Committee/Institutional Review Board and scientific peer-review. We expect that, measured against these standards, some donor-funded research would be acceptable.